1991
DOI: 10.1161/01.atv.11.5.1303
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between variant apolipoproteins C-II and E that affects plasma lipoprotein concentrations.

Abstract: The genes for apolipoprotein (apo) C-II, a cofactor for activation of lipoprotein lipase, and apo £, a ligand for receptor-mediated uptake of triglyceride-rich lipoproteins, are physically linked on chromosome 19ql3.1. In a large Caribbean Caucasian family, several individuals had clinical features of the complete absence of lipoprotein lipase activity and were homozygous for a DNA frameshift mutation of apo C-II, imparting functional inactivity to the mutant protein.Plasma from heterozygous carriers of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…18 Furthermore, the presence of a single APOE E4 allele occurring in individuals with a single, mutant apo CII-T allele has been associated with higher plasma concentrations of cholesterol, TGs, and VLDL cholesterol when compared with relatives who carried neither or only 1 variant allele. 21 The data from the current report suggest that although routine biochemical tests might have been adequate to detect the association of apo CII-T with elevated plasma TGs, only the more labor-intensive procedure of ultracentrifugation of plasma would have permitted detection of the more subtle finding of increased LDL TGs for both of these mutations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…18 Furthermore, the presence of a single APOE E4 allele occurring in individuals with a single, mutant apo CII-T allele has been associated with higher plasma concentrations of cholesterol, TGs, and VLDL cholesterol when compared with relatives who carried neither or only 1 variant allele. 21 The data from the current report suggest that although routine biochemical tests might have been adequate to detect the association of apo CII-T with elevated plasma TGs, only the more labor-intensive procedure of ultracentrifugation of plasma would have permitted detection of the more subtle finding of increased LDL TGs for both of these mutations.…”
Section: Discussionmentioning
confidence: 71%
“…18 Heterozygotes for apo CII-T have an Ϸ50% decrease in apo CII mass and capacity to activate LPL. 21 The association of heterozygosity for apo CII-T with higher total TGs and LDL TGs suggests that impairment of this pathway can affect lipoprotein quantity and composition. The absence of associations of lipoprotein phenotypes with compound heterozygosity for both mutations was likely due to small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…40 Similarly, analysis of pedigrees of probands with familial chylomicronemia attributable to mutant apoC-II isoforms suggested that obligate heterozygote carriers of APOC2 mutations had elevated plasma TG and high TG content in lipoprotein subfractions. 41 Finally, heterozygous relatives of probands homozygous for truncating mutations in APOA5 and severe HTG were variably found to have moderately elevated plasma TG. 42,43 Thus, evidence from the pre-and postgenomic eras, including findings from this study, indicates that heterozygosity for rare dysfunctional coding sequence mutations is strongly associated with severe HTG.…”
Section: Discussionmentioning
confidence: 99%
“…When OHLD family members (excluding unrelated spouses) were classified 40.5 ±18.3 years), mean levels of HDL TG were not above the 95th percentile in carriers of T383M and S267F, whereas mean levels of LDL TG exceeded the 95th percentile for carriers of S267F but not for carriers of T383M. When "hyperbetatriglyceridemia" and "hyperalphatriglyceridemia" are used to define the phenotype in subjects with levels of LDL TG and HDL TG, respectively, that exceed the 95th percentile for age and sex, then all compound heterozygotes have hyperalphatriglyceridemia and hyperbetatriglyceridemia.…”
Section: Lipoprotein Phenotypes and Hl Genotypesmentioning
confidence: 99%